2010
DOI: 10.1093/mp/ssq027
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Biochemical and Molecular Networks Involved in Maize Cell Habituation to the Cellulose Biosynthesis Inhibitor Dichlobenil

Abstract: The biochemical and molecular processes involved in the habituation of maize cells to growth in the presence of the cellulose biosynthesis inhibitor dichlobenil (DCB) were investigated. DCB affects the synthesis of cellulose both in active and stationary growth phases and alters the expression of several CesA genes. Of these, ZmCesA5 and ZmCesA7 seem to play a major role in habituating cells to growth in the presence of DCB. As a consequence of the reduction in cellulose, the expression of several genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 67 publications
3
51
2
Order By: Relevance
“…This alcohol insoluble residue (AIR) was dried at 60ºC for 2 days. AIR was then de-starched, treated with acidified phenol and washed with organic solvents to obtain the cell wall residue as previously described [54,55].…”
Section: Cell Wall Analysismentioning
confidence: 99%
“…This alcohol insoluble residue (AIR) was dried at 60ºC for 2 days. AIR was then de-starched, treated with acidified phenol and washed with organic solvents to obtain the cell wall residue as previously described [54,55].…”
Section: Cell Wall Analysismentioning
confidence: 99%
“…This is the case of bean cell cultures where habituation to dichlobenil is associated with high class III-per (García-Angulo et al, 2009). In the case of maize cells, an increased antioxidant capacity seems to take part in changes associated to the incipient dichlobenil-habituation process (Largo-Gosens et al, 2016), however, antioxidant activities are not implicated in the long-term habituation to high dichlobenil concentrations (Mélida et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…By compositional analysis and structural characterization of the cell walls of DCB‐habituated cells, it has been demonstrated that maize cells have the capacity to cope with DCB through acquisition of a modified cell wall. In DCB‐habituated cells, cellulosic scaffold was partially replaced by a more extensive network of highly cross‐linked feruloylated arabinoxylans (Mélida et al , , , , , de Castro et al , , Largo‐Gosens et al ). Recently, it has been shown that DCB‐habituated maize cells incorporate to the cell walls lignin‐like polymers (Mélida et al ), which stiffens the structure further (Pomar et al , Kärkönen and Kuchitsu ).…”
Section: Introductionmentioning
confidence: 99%